Propuesta de intervención en el ámbito del ocio y tiempo libre de usuarios/as de COCEMFE Cáceres. - Rebolledo Gutiérrez, Juan Carlos; Rohlfs Domínguez, Paloma (Revista Española de Discapacidad, 2014)
Rebolledo Gutiérrez, J.C. y Rohlfs Domínguez, P. (2014): “Propuesta de intervención en el ámbito del ocio y tiempo libre de usuarios/as de COCEMFE Cáceres”. Revista Española de Discapacidad, 2 (1): 223-231.